Analyzing environmental factors that favor the growth of the invasive brown macroalga Rugulopteryx okamurae (Ochrophyta): The probable role of the nutrient excess. (January 2022) - Mercado, Jesús M.; Gómez-Jakobsen, Francisco; Korbee, Nathalie; Aviles, Antonio; Bonomi-Barufi, José; Muñoz, María; Reul, Andreas; Figueroa, Félix L.
Abstract: Time series of temperature, salinity and nutrients in the Strait of Gibraltar (SoG) were researched to analyze which factors explain the invasive success of Rugulopteryx okamurare, which has colonized wide coastal areas at the Spanish and Moroccan coasts since 2016. Temperature and salinity were higher in the SoG compared to its native habitat, implying that the alga is active during the whole seasonal cycle and grows optimally at the high salinities occurring in the SoG. Nitrate removal experiments indicate that the alga is able to linearly increase its N uptake rates following boost in nitrate concentration. Furthermore, R . okamurae N content ranged from 1.4% to 4.5% suggesting that this species has high N storage capacity potentially usable when the external N concentration decreases. These physiological characteristics would explain sharp growth of the alga in the SoG where high N concentrations are registered occasionally. Highlights: The brown alga Rugulopteryx okamure invades the coast area of the Strait of Gibraltar since 2016 High capacity for nitrate removal contribute to the invasive success of this species Temperature, salinity and nutrient conditions in the Strait of Gibraltar explain its invasive success These conditions are common in wide areas of the Mediterranean and Atlantic Sea where R.okamurae represents a serious threat